Thematic analysis: factors of food safety certification adoption among farmers in Malaysia - Mohd Shahir, Omar; Muhammad Fakhrul, Yusuf; Cheng, Jack Kie (Emerald Publishing Limited 1477-0024, 2023)
Purpose – This study aims to identify the factors to food safety certification adoption among farmers in Malaysia. Design/methodology/approach – This study was conducted qualitatively using a method of interviewing with unstructured questions. To identify the factors that influence and prevent the adoption of food safety certification among Malaysian farmers, nine (n ¼ 9) agricultural industrial experts were randomly chosen. Findings – Based on data analysis using thematic analysis, the respondent highlighted 14 factors to food safety certification. Specifically, the most frequent determinant highlighted by the respondent is enforcement (12). Additionally, it has been proven that the identified factors aligned with existing theories: technology, organization and environment (TOE) framework and eco-innovation theory. These theories help researchers to create effective strategies and produce significant findings from their research. Originality/value – To the best of the authors’ knowledge, this study is the first to investigate food safety certification adoption among farmers in the Malaysian agriculture industry using the integration of the TOE framework and eco-innovation theory. The stakeholder is expected to receive the benefits of creating efficient campaigns to encourage more farmers to obtain food safety certification. This study provides further knowledge by improving the understanding of the processes involved in certification adoption, providing context-specific insights, best practices, policy guiding development and emphasizing the effects of certification on sustainability and competitiveness.